HER2 somatic mutations are associated with poor survival in HER2‐negative breast cancers. Issue 4 (21st April 2017) - Wang, Tonghui; Xu, Ye; Sheng, Shuyan; Yuan, Hua; Ouyang, Tao; Li, Jinfeng; Wang, Tianfeng; Fan, Zhaoqing; Fan, Tie; Lin, Benyao; Xie, Yuntao
Abstract : It is well documented that human epidermal growth factor receptor 2 (HER2) overexpression/amplification is associated with poor survival in breast cancer patients. However, it is largely unknown whether HER2 somatic mutations are associated with survival in HER2‐negative breast cancer patients. Here, we identified HER2 somatic mutations in tumors from 1348 unselected breast cancer patients by sequencing the entire HER2 coding region. All of these mutations were tested for in corresponding blood samples to determine whether they were somatic or germline mutations. We further investigated the associations between HER2 somatic mutations and recurrence‐free survival and distant recurrence‐free survival in this cohort of patients. We found that 27 of 1348 (2.0%) of these patients carried a HER2 somatic mutation. In vitro experiments indicated that some of the novel mutations and those with unknown functions increased HER2 activity. HER2 status was available for 1306 patients, and the HER2 somatic mutation rates in HER2‐positive ( n = 353) and HER2‐negative breast cancers ( n = 953) were 1.4% and 2.3%, respectively. Among the HER2‐negative patients, those with a HER2 somatic mutation had a significantly worse recurrence‐free survival (unadjusted hazard ratio = 2.67; 95% confidence interval, 1.25–5.72, P = 0.002) and distant recurrence‐free survival (unadjusted hazard ratio = 2.50; 95% confidence interval, 1.10–5.68, P = 0.004) than those with wild‐type HER2 . Taken together, our findings suggested that HER2 somatic mutations occur at a higher frequency in HER2‐negative breast cancer, and HER2‐negative breast cancer patients with these mutations have poor survival. Therefore, HER2‐negative patients with a HER2 somatic mutation are potentially good candidates for HER2‐targeted therapy. Abstract : We identified HER2 somatic mutations in tumors from 1348 unselected breast cancer patients by sequencing the entire HER2 coding region. Here, we are first to report that HER2‐negative breast cancer patients with HER2 somatic mutation have an unfavorable survival. Therefore, HER2‐negative patients with HER2 somatic mutation are potentially good candidates for HER2‐targeted therapy or for recruitment into ongoing clinical trials.